Genetic predisposition to coronary artery disease in type 2 diabetes - van Zuydam, NR; Ladenvall, C; Voight, BF; Strawbridge, RJ; Fernandez Tajes, J; Rayner, NW; Robertson, NR; Mahajan, A; Vlachopoulou, E; Goel, A; Kleber, ME; Nelson, CP; et al. (Lippincott, Williams & Wilkins, 2020)
Background - Coronary artery disease (CAD) is accelerated in subjects with type 2 diabetes (T2D).